X-ray surveys of active galactic nuclei in field and cluster environments - Johnson, Olivia (The University of Edinburgh, 2004)
In recent years, the Chandra and XMM-Newton observatories have provided an unprecedented view of the X-ray sky, with deep surveys resolving the majority of the X-ray flux in the Universe for the first time. This thesis presents three multiwavelength surveys of different environments based on deep X-ray observations, which together aim to develop our understanding of Active Galactic Nuclei (AGN) and their role within the evolution of galaxies and their larger-scale environment.

I present results of the ELAIS Deep X-ray Survey (EDXS), an early C handra ‘blank field’ survey designed to characterise the components of the XRB and to study their relation to populations detected in other wavebands. Between 50-64% of the XRB is resolved into sources detected in the two EDXS fields which are optically identified as quasars, bright galaxies, and optically faint sources. The X-ray spectral properties of the sources indicate that those with optically faint and galaxy morphology are likely to house a large population of obscured AGN as predicted by synthesis models of the XRB. These optically resolved sources have fainter X-ray and optical fluxes, harder X-ray spectra, redder optical colours, and more scatter in their X-ray to optical ratios than the quasars in the sample, which is in general consistent with X-ray obscuration o f nuclear light in sources in which the host galaxy dominates the optical properties. Detailed comparison of the X -ray and optical/near-IR spectra of selected E D X S sources indicates substantial variety in source morphology and in relative obscuration by gas and dust in the obscured AG N population.

I have conducted an analysis of the AGN content of the 2 = 0.83 galaxy cluster MS 1054- OS based on archival Chandra data. I detect 47 X-ray point sources in the MS1054-03 field, of which two are confirmed from pre-existing spectroscopy to be luminous AGN at the redshift of the cluster. At bright fluxes, I find a 2δ excess of point sources compared to the predictions from field surveys, consistent with ~ 6 additional cluster AGN. Combined with the identification of 7 cluster AGN in deep radio observations, these observations suggest significantly enhanced AGN activity in MS1054-03 compared to local galaxy clusters. The excess of X-ray detected AGN is found at radial distances of 1 to 2 Mpc from the cluster centre, suggesting they may be associated with infalling galaxies. The radio AGN are seen within the inner Mpc of the cluster and are largely undetected in the X-ray, suggesting they are either intrinsically less luminous and/or heavily obscured.

I have surveyed the SSA 22 protocluster at z = 3.09 using both extremely deep XMM-Newton imaging data and narrow-band wide-field Lycv observations of the field. I detect 29 new candidate Lyα emitters and 190 X-ray sources in the region. A Lyman Break Galaxy (LBG) and two Lyα candidates are detected in the X-ray, hosting quasars with estimated bolometric luminosities of ~10⁴⁶ erg s⁻¹ . The observed AGN fractions of LBGs and Lyα candidates in SSA 22 are ~4% and ~1.3%, respectively. Stacking analysis of the LBG, Lyα candidate, and submillimetreselected samples in the field do not result in significant detections, and limit the average hard X-ray luminosity of each type of source to ~5 x 10⁴³ erg s⁻¹. There is no evidence of diffuse X-ray emission associated with the protocluster as a whole or with luminous, diffuse regions of Lyα flux in the structure. Soft band X-ray flux on scales of ~1 Mpc is limited to L₀.₅₋₂keV ≲ 9 x 10⁴³ erg s⁻¹ , robustly excluding all but the faintest thermal emission seen in local clusters. On smaller scales of ~ 0.6 Mpc which may be more typical of high redshift clusters, the limit is L₀.₅₋₂keV ≲ 3 x 10⁴³ which just excludes the level of emission seen in clusters at z ~ 1.3. The limit on thermal X-ray emission associated with the diffuse Lyα emission, is L₀.₅₋₂keV ≲ 1 x 10⁴² erg s⁻¹ . Point source limits in these regions exclude A G N with obscuring columns of NH ≲ 10²³ cm⁻² to L₀.₅₋₈keV ≲ 3 x 10⁴³ erg s⁻¹ , and all but Compton thick sources to L₀.₅₋₈keV ≲ 10⁴⁵ erg s⁻¹.